“Batalam” as a Minangkabau Tradition in Andaleh Village, Luak Sub-District Limapuluh Kota District - Indrawati (LEGAL BRIEF, 2021)
The "Batalam" tradition is one part of Minangkabau customs, especially in the Kanagarian Andaleh community, Luak District, Limapuluh Kota Regency. Until now, the batalam tradition has not been contaminated by external values and its existence is still maintained by the community. The research, entitled: Batalam Tradition in Minangkabau Society in Kanagarian Andaleh, Luak District, Limapuluh Kota Regency, wants to know the meaning of Batalam tradition for the Kanagarian Andaleh community and analyze public perceptions of the implementation of the Batalam tradition in Kanagarian Andaleh. This type of research is categorized as qualitative research so that the research informants are community leaders consisting of traditional leaders, religious leaders, and other community leaders including mothers and youth leaders who are considered to understand the meaning and are directly involved in the implementation of the batalam custom in Kanaagarian Andaleh which was taken using the Snowball sampling technique. Batalam as a form of relationship that is bound by the norm of reciprocity and as social capital. People do not consider these rights as a heavy burden that is difficult to realize, because of the subsistence ethic that is still alive and becomes values that can still be realized. It is hoped that the community members together with community leaders in Kanagarian Andaleh will try to maintain the positive values contained in the batam tradition.